2021
DOI: 10.3389/fncir.2021.649417
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Dynamic Functional Connectivity of Default Mode Network in Schizophrenia and Links to Symptom Severity

Abstract: Background: Schizophrenia affects around 1% of the global population. Functional connectivity extracted from resting-state functional magnetic resonance imaging (rs-fMRI) has previously been used to study schizophrenia and has great potential to provide novel insights into the disorder. Some studies have shown abnormal functional connectivity in the default mode network (DMN) of individuals with schizophrenia, and more recent studies have shown abnormal dynamic functional connectivity (dFC) in individuals with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
84
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 60 publications
13
84
2
Order By: Relevance
“…Using a data-driven method of analyzing dFNC in CCN and DMN, we demonstrated that these brain networks are highly dynamic in both pre- and post-ECT states. This finding agrees with previous studies on MDD that have provided evidence of dynamism in CCN and DMN (Repple et al, 2020 ; Yang et al, 2020 ; Chen et al, 2021 ; Sendi et al, 2021a ). Previous studies differentiated MDD from the HC group, focusing on within-DMN and within-CCN functional connectivity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Using a data-driven method of analyzing dFNC in CCN and DMN, we demonstrated that these brain networks are highly dynamic in both pre- and post-ECT states. This finding agrees with previous studies on MDD that have provided evidence of dynamism in CCN and DMN (Repple et al, 2020 ; Yang et al, 2020 ; Chen et al, 2021 ; Sendi et al, 2021a ). Previous studies differentiated MDD from the HC group, focusing on within-DMN and within-CCN functional connectivity.…”
Section: Discussionsupporting
confidence: 93%
“…Calculated dFNC for each window was concatenated for each subject as a form of C × C × T array (where C is the number of ICs and equals 276, and T represents total windows and equals 610). Finally, all arrays for all subjects were concatenated to show brain connectivity changes between ICs as a function of time ( Figure 1 , Step 2) (Allen et al, 2014 ; Sendi et al, 2021a , b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resting-state fMRI-based dynamic FC analysis may be employed to reflect the dynamic properties of brain function as well as improve our understanding of brain development/maturation/aging ( Chen et al, 2018 ) and cognitive-behavioral ( Nomi et al, 2017 ) mechanisms. Furthermore, the utilization of dynamic FC analysis enables us to elucidate the mechanisms underlying several psychiatric and neurological disorders such as schizophrenia ( Sendi et al, 2021a ) and Alzheimer’s disease ( Sendi et al, 2021b ). Several studies have assessed FC changes in ALS using a dynamic point of view.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a new line of research called dynamic functional network connectivity (dFNC) have moved beyond studying the strength of connectivity among brain regions and studied the temporal properties of the FNC (Allen et al, 2014). dFNC has shown promise as a biomarker for schizophrenia (Sendi et al, 2021a, 2021b), Alzheimer’s disease (Sendi et al, 2021c), major depressive disorder (Sendi et al, 2021e), and autism spectrum disorder (Harlalka et al, 2019). It has been shown that dFNC improves classification between disordered and healthy conditions (Rashid et al, 2015; Saha et al, 2021) and provides more information about the pathology of neurological and neuropsychiatric disorders than its static counterpart (Menon and Krishnamurthy, 2019).…”
Section: Introductionmentioning
confidence: 99%